Somatic embryogenesis from the axillary meristems of peanut (Arachis hypogaea L.) - Singh, Shweta; Hazra, Sulekha (Plant Biotechnology Reports, 2009)
Developmental anomalies in the plumule meristem of peanut (Arachis hypogaea L.) somatic embryos resulted in poor shoot differentiation and reduced plant recovery. Existing meristems with caulogenic potential have never been tested for embryogenesis in peanut. The present experiment was designed to test the mature zygotic embryo axis derived plumule with three meristems for somatic embryogenesis. Embryogenic masses and embryos developed from the caulogenic meristems in the axils. Exposure of 2 weeks in primary medium with 90.5 A mu M 2,4-D suppressed the shoot tip differentiation temporarily which then regained the ability to form the shoot on withdrawal of 2,4-D. Exposure of 4 weeks in primary medium with 90.5 A mu M 2,4-D suppressed the shoot tip differentiation irreversibly. No shoot formation was noted from the tips in any of the cultures which were in secondary medium with 13.6 A mu M 2,4-D. Development of somatic embryos directly from axillary meristems was confirmed histologically. Conversion frequency of these embryos was 11%. Thus, in this report, we describe a method to obtain somatic embryos from the determined organogenic buds of the axillary meristem, by culturing the nodal explant vertically on embryo induction medium. It also displays the possibility of obtaining both embryogenic and organogenic potential in two parts of the same explant simultaneously. The possibility of extending this approach for genetic transformation in in vivo system through direct DNA delivery or Agrobacterium injection in meristems can also be explored. Using Agrobacterium rhizogenes, we have demonstrated the possibility of gene transfer in the axillary meristems of seed-derived plumule explant.
Keywords: Apical meristem; Axillary meristem; Mature zygotic embryo axis; Peanut; somatic embryogenesis

Synthesis of gold nanoparticles by various leaf fractions of Semecarpus anacardium L. tree - Raju, D.; Mehta, Urmil J.; Hazra, Sulekha (Trees-Structure and Function, 2011)
Gold nanoparticles (NPs) were synthesized using Semecarpus anacardium leaf extracts in water and the green biomass. Extract prepared at ambient condition by crushing the leaves in deionized water is identified as `green extract', and that by boiling the leaf pieces as `boiled extract'. The mass remaining after separating the `green extract' is identified as `green biomass'. These components triggered rapid reduction of Au(III) to Au (0) in HAuCl4 solution indicating the natural ability of the leaves of S. anacardium to synthesize NPs in ambient conditions. Green extract produced more NPs compared to the boiled extract suggesting denaturization of some of the useful factors due to boiling. NPs were quantified using UV and ICP-AES analysis. These were characterized using Transmission electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction. TEM images of the particles formed with green extract, boiled extract and green biomass showed that the particles were of different shapes and sizes.
Keywords: Biosynthesis; gold nanoparticles; Green extract; Semecarpus; TEM